How I manage a patient with MRSA bacteraemia. (February 2022) - Davis, Joshua S.; Petersiel, Neta; Tong, Steven Y.C.
Abstract: Background: Staphylococcus aureus bloodstream infections are common and associated with a high mortality of 15–25%. Methicillin-resistant S. aureus (MRSA) bloodstream infection accounts for 10–40% of cases, and has an even higher mortality. Despite being the 'bread and butter' of clinical infectious diseases practice, robust evidence to guide optimal management is often lacking and there is wide variation in practice. Objectives: To provide a real-world example of a case of MRSA bacteraemia and the thought processes of the authors as key management decision points are reached. Sources: The discussion is based on recent literature searches of relevant topics. In making recommendations, randomized clinical trial data have been prioritized and highlighted, and where these are not available recommendations are based on the experience and opinions of the authors. Content: For a patient with MRSA bacteraemia and a primary bone and joint infection the following points are discussed: empirical antibiotic choice for suspected S. aureus bacteraemia; directed antibiotic choice for MRSA; monitoring and dosing of vancomycin; the role of combination therapy when bacteraemia is persistent; and the duration of therapy and role of switching to oral antibiotics. Implications: While broad principles of aggressive source control and appropriate choice and duration of antibiotics are important, the heterogeneity of S. aureus bacteraemia means that a tailored rather than algorithmic approach to management is often required. Further randomized controlled trials are needed to strengthen the evidence base for the management of MRSA bacteraemia.